2017
DOI: 10.1039/c7ra04435f
|View full text |Cite
|
Sign up to set email alerts
|

Micro-solvation of tyrosine-kinase inhibitor AG1478 explored with fluorescence spectroscopy and computational chemistry

Abstract: Fluorescence quenching of the anticancer AG1478, by at least three explicit water molecules, can be exploited to probe drug–protein binding interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…A decrease in fluorescence due to an increase in temperature is expected based on an increase in the nonradiative rates of deactivation from the excited state or dynamic quenching processes. An increase in fluorescence with temperature is unusual but was reported by us previously for the AG1478–water complex in acetonitrile/water solutions because of a release of static quenching . This unorthodox temperature dependence of emission could be tentatively explained by both static and dynamic quenching mechanisms in the binding site of the protein or a temperature-dependent conformational change.…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…A decrease in fluorescence due to an increase in temperature is expected based on an increase in the nonradiative rates of deactivation from the excited state or dynamic quenching processes. An increase in fluorescence with temperature is unusual but was reported by us previously for the AG1478–water complex in acetonitrile/water solutions because of a release of static quenching . This unorthodox temperature dependence of emission could be tentatively explained by both static and dynamic quenching mechanisms in the binding site of the protein or a temperature-dependent conformational change.…”
Section: Resultssupporting
confidence: 52%
“…An increase in fluorescence with temperature is unusual but was reported by us previously for the AG1478− water complex in acetonitrile/water solutions because of a release of static quenching. 53 This unorthodox temperature dependence of emission could be tentatively explained by both static and dynamic quenching mechanisms in the binding site of the protein or a temperature-dependent conformational change. However, we note that more work is needed to properly explain this behavior.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Our own studies on AG1478 have revealed that the spectroscopic properties are sensitive to both environment 53 , 54 and AG1478 conformational state 55 . For example, two conformers- one planar and the other twisted- were identified based on quantum chemical calculations and experimental absorption spectra 55 .…”
Section: Introductionmentioning
confidence: 99%